Potensi Jus Buah Pepaya (Carica Papaya L.) Mencegah Nefrotoksisitas pada Tikus Wistar yang Terpapar Pb Asetat - Devi Etivia Purlinda; Sorta Basar Ida Simanjuntak; Saryono Saryono (Fakultas Biologi | Universitas Jenderal Soedirman, 2020)
Lead is a heavy metal with hazardous toxicity causing dysfunction, especially the kidneys as excretion organs. Pb pollution in Indonesia is mostly derived from transportation emissions such as Tetraetillead, which can change into trietillead, a free radical that can reduce endogenous enzyme activity, one of which is SOD pollution. (Superoxide dismutase) which is in various organs, especially the kidneys. A decrease in SOD activity in the kidneys indicates oxidative stress because the enzyme is unable against superoxide anions and causes renal glomerular damage. Kidney damage can increase serum creatinine levels. Papaya juice contains flavonoids, vitamins C, E, and beta-carotene can prevent nephrotoxicity of Pb. The study aimed to obtain the best dose of papaya juice on the SOD activity of Wistar rats kidney tissue and serum creatinine level that exposed by lead acetate. The experiment was conducted experimentally with Completely Randomized Design, which was divided into 6 treatments, P1, P2, P3, of papaya juice, Lead ace with dose: 3.6; 7.2; 14.4 g / 200g of weight and exposed to Pb acetate 50 mg/kg weight. Treatment P4 (rats were given vitamin E 400 IU/kg weight and exposure to Pb acetate 50 mg/kg weight), P5 (rat exposed Pb acetate 50 mg/kg weight), P6 (normal mice) for 28 days. The results showed that papaya juice was the best dose of 14.4 g / 200g weight because the SOD activity of renal tissue was increased, and serum creatinine level decreased significantly. The conclusion is papaya juice can be used to prevent Pb acetate nephrotoxicity.